2021
DOI: 10.1016/j.eclinm.2021.100975
|View full text |Cite
|
Sign up to set email alerts
|

Centenarians and extremely old people living with frailty can elicit durable SARS-CoV-2 spike specific IgG antibodies with virus neutralization functions following virus infection as determined by serological study

Abstract: Background The SARS-CoV-2 (Severe Acute Respiratory Syndrome coronavirus 2) has led to more than 165 million COVID-19 cases and >3.4 million deaths worldwide. Epidemiological analysis has revealed that the risk of developing severe COVID-19 increases with age. Despite a disproportionate number of older individuals and long-term care facilities being affected by SARS-CoV-2 and COVID-19, very little is understood about the immune responses and development of humoral immunity in the extremely old per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…Such observations support the role of the humoral response against SARS-CoV-2. Our data corroborate a study by Foley and Colleagues, which reported higher anti-spike IgG antibody titers in nonagenarians and centenarians exposed to SARS-CoV-2 in a long-term care home (n = 15) than in younger individuals living in the same environment [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such observations support the role of the humoral response against SARS-CoV-2. Our data corroborate a study by Foley and Colleagues, which reported higher anti-spike IgG antibody titers in nonagenarians and centenarians exposed to SARS-CoV-2 in a long-term care home (n = 15) than in younger individuals living in the same environment [27].…”
Section: Discussionsupporting
confidence: 92%
“…Despite that, worldwide reports of unvaccinated centenarians and supercentenarians (105 years or older) recovered from Covid-19 with mild or moderate symptoms called our attention [25][26][27][28][29]. Understanding why some individuals overcome the disease despite aging, such as the nun Ms. Randon, the oldest person already reported to survive Covid-19 at age 116 [30] is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Further interesting results have been obtained from the study of anti-S neutralising antibodies. A study conducted on centenarians residing in long-term care facilities had already demonstrated that an aged immune system is still capable of producing an antibody response to SARS-CoV-2 infection, and that the antibodies produced had neutralising abilities [27]. Our data con rmed this and additionally showed that the levels of produced antibodies were slightly higher than those produced by seventy-year-old individuals, although the difference was not signi cant.…”
Section: Discussionsupporting
confidence: 82%
“…As an important example, metabolic inflammation [ 1039 ], due to the accumulation of adipose tissue, contributes to the observed inflammatory phenotype in frail individuals [ 1031 ]. Although frail individuals have functional adaptive immune responses after SARS-CoV-2 infection [ 1041 ] and vaccination [ 1042 , 1043 ], faster waning of IgG levels [ 1044 , 1045 ] and immune-senescent memory T cell functions [ 1046 ] indicates that immune memory might be less durable compared to in non-frail individuals.…”
Section: Interactions Between Effectsmentioning
confidence: 99%